Henry James and Queer Aesthetics: Roderick Hudson. - Hueso-Vasallo, Manuel (My University, 2022)
In her ground-breaking work Queer Phenomenology (2006), Sara Ahmed established that “[o]rientations are about the direction we take that puts some things and not others in our reach” (56). Following this trend of thought, this seminar addresses the potential benefits of combining Queer studies and Victorian literature to inspect and study alternative approaches to the ways in which dissident sexualities have been articulated outside of the legal and medical discourses by analysing Henry James's Roderick Hudson (1875).
Keywords: James, Henry - Crítica e interpretación; Teoría queer; Estética literaria; Henry James; Aestheticism; Queer studies